Optimalisasi lahan milik pemerintah untuk keadilan akses rumah terjangkau MBR - Mutaqi, Ahmad Saifudin; Salura, Purnama; Lake, Reginaldo Christophori (EMARA: Indonesian Journal of Architecture, 2023)
Indonesia's population growth has slowed, yet low-income people still require affordable urban housing. Land scarcity, limited financial options, and complicated home funding provide significant challenges. This study analyses existing literature to find ways to provide cheap housing to Indonesian middle-class residents. The study examines land use, financing, and cash availability. The findings show that MBR cannot get funding due to high costs and strict criteria, while the scarcity of urban land is hindering development. The analysis recommends using unused government land and promoting vertical housing to maximise land use, investigating microfinance and lease-purchase schemes, and simplifying housing fund access. These hurdles can be overcome to provide fair and affordable housing for all in Indonesia, promoting social stability and sustainable urban expansion.